PERAN PERSEPSI OTENTISITAS, PERSEPSI NILAI, PERSEPSI RISIKO DAN KEPUASAN KONSUMEN TERHADAP NIAT PEMBELIAN KEMBALI PADA AIRBNB DAN HOTEL DI BALI - Ermawati; Santi Budiman; Arif Siaha Widodo; Damiasih Damiasih (Jurnal Perilaku dan Strategi Bisnis, 2025)
Airbnb has become a serious competitor to conventional hotels in the sharing economy. This study aims to compare the factors influencing customer satisfaction and repurchase intentions among Airbnb and hotel users in Bali. Using a survey method with 230 respondents, the factors examined included perceived authenticity, perceived value, and perceived risk. The results showed that perceived authenticity and perceived risk had a positive and significant influence on customer satisfaction. Meanwhile, perceived risk did not have a significant negative influence. Other findings indicate that customer satisfaction positively and significantly influenced repurchase intentions. While there was a significant difference in satisfaction levels between Airbnb and hotel users, there was no significant difference in repurchase intentions between the two groups.